Development of a Nursing Care Protocol for Patients Undergoing Microsurgical Breast Reconstruction (Estima – Brazilian Journal of Enterostomal Therapy, 2026)
Objective: To develop a nursing protocol for the care of patients undergoing microsurgical breast reconstruction. Method: This methodological study used a qualitative approach and adopted the Transitions Theory as its theoretical framework. The protocol development followed the criteria established by the Federal Nursing Council and the phases of Convergent Care Research, with the participation of three nurses and the use of data from 25 women. The International Classification for Nursing Practice (ICNP®) was used as the terminology system for documentation. Results: The protocol comprises 17 nursing diagnoses, 17 nursing outcomes, and 29 nursing interventions mapped according to the ICNP®. In addition, it includes guidance for the care of patients in the postoperative period following microsurgical breast reconstruction. Conclusion: The protocol is a technological tool with the potential to contribute to the field. Its use is expected to enhance patient safety by preventing complications and hospital readmissions. The use of standardized terminology for documentation should also enhance the visibility of nurses’ work.